2015
DOI: 10.1038/oncsis.2015.28
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA mutations can initiate pancreatic tumorigenesis and are targetable with PI3K inhibitors

Abstract: Aberrations in the phosphoinositide 3-kinase (PI3K) signaling pathway have a key role in the pathogenesis of numerous cancers by altering cell growth, metabolism, proliferation and apoptosis. Interest in targeting the PI3K signaling cascade continues, as new agents are being clinically evaluated. PIK3CA mutations result in a constitutively active PI3K and are present in a subset of pancreatic cancers. Here we examine mutant PIK3CA-mediated pancreatic tumorigenesis and the response of PIK3CA mutant pancreatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 42 publications
(53 reference statements)
1
46
0
Order By: Relevance
“…In line with this finding, ADM, PanIN and the formation of invasive PDAC can also be observed after transgenic expression of a constitutively-active form of p110α 82 . PI3K-mediated transdifferentiation of acinar cells is mediated through ERK1/2 signalling 82 , and small molecule inhibitors targeting the activation of ERK1/2 indicate that these MAP kinases are involved in Kras G12D -driven dedifferentiation of acinar cells, ADM and PanIN formation 11,83 . To drive these processes, PI3K also initiates actin reorganization processes that are orchestrated by Rho GTPases 80,81,84 .…”
Section: Oncogene-driven Irreversible Admsupporting
confidence: 70%
“…In line with this finding, ADM, PanIN and the formation of invasive PDAC can also be observed after transgenic expression of a constitutively-active form of p110α 82 . PI3K-mediated transdifferentiation of acinar cells is mediated through ERK1/2 signalling 82 , and small molecule inhibitors targeting the activation of ERK1/2 indicate that these MAP kinases are involved in Kras G12D -driven dedifferentiation of acinar cells, ADM and PanIN formation 11,83 . To drive these processes, PI3K also initiates actin reorganization processes that are orchestrated by Rho GTPases 80,81,84 .…”
Section: Oncogene-driven Irreversible Admsupporting
confidence: 70%
“…In addition, recent large-scale, pan-cancer proteogenomic studies have identified molecular alterations in several Src effector networks including PI3K/Akt/ mTOR and FAK [80,[126][127][128]. The PI3KCA gene mutations present in 3-5% of pancreatic cancer patients can act as activating mutations initiating pancreatic tumour formation [129]. In PDAC specifically,~17% of tumours carried alterations, the majority of which involved gene amplification, and this finding is consistent across multiple cohorts [114,115] (Fig.…”
Section: The Src Signalling Axis Promotes Pancreatic Cancer Progressionmentioning
confidence: 57%
“…Pancreatic cancer is one of the most aggressive solid malignancies with an extremely poor prognosis of an overall 5-year survival rate of <5% [1]. Without a specific diagnostic marker and symptom in early stage, pancreatic cancer is often diagnosed at an advanced/late stage and only palliative measures can be offered [2].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrations of the PI3K signaling induces the pathogenesis of numerous cancers by altering cell growth and apoptosis [1]. Vichalkovski et al have reported that activation of AKT upregulated the expression of Twist, subsequently decreasing chemotherapy-induced DNA damage, and inhibiting apoptosis [21].…”
Section: Introductionmentioning
confidence: 99%